Operation of a single-photon-counting x-ray charge-coupled device camera spectrometer in a petawatt environment - Stoeckl, C; Theobald, W; Sangster, T; Key, M; Patel, P; Zhang, B; Clarke, R; Karsch, S; Norreys, P (2004)
The use of a single-photon-counting x-ray charge-coupled device (CCD) camera as an x-ray spectrometer is a well-established technique in ultrashort-pulse laser experiments. In single-photon-counting mode, the pixel value of each readout pixel is proportional to the energy deposited from the incident x-ray photon. For photons below 100 keV, a significant fraction of the events deposits all the energy in a single pixel. A histogram of the pixel readout values gives a good approximation of the x-ray spectrum. This technique requires almost no alignment, but it is very sensitive to signal-to-background issues, especially in a high-energy petawatt environment. Shielding the direct line of sight to the target was not sufficient to obtain a high-quality spectrum, for the experiments reported here the CCD camera had to be shielded from all sides with up to 10 cm of lead. © 2004 American Institute of Physics.